Business-centric inventory Modelling: Constant deterioration, constant demand and partial backlogging - Shilpi Singh,; Ashish Agarwal,; Khursheed Alam, (Utilitas Mathematica, 2025)
This paper presents a deterministic inventory model addressing the challenges of cost optimization in business-centric inventory systems. The proposed model incorporates a constant rate of deterioration and considers demand as a quadratic function of time. Partial backlogging is allowed for shortages. The primary objective is to minimize the average total cost by optimizing key decision variables. The analytical model is supported by numerical simulation using MATLAB to determine inventory dynamics, cost components, and optimal conditions. Sensitivity analysis is also conducted to evaluate the impact of variations in model parameters. The study highlights the significance of integrating soft computing with inventory control to achieve business efficiency.